‘Welcoming the stranger’ and UNHCR’s cooperation with faith-based organisations - Riera, J; Poirier, M (Refugee Studies Centre, University of Oxford, 2014)
Since its creation in 1950, UNHCR has engaged with faith-based organisations, faith communities and faith leaders in carrying out its work. Recently, UNHCR has been more actively exploring the role of faith in humanitarian responses